Ventricular arrhythmias in a pregnant female – clinical implications - Nowak, Ewelina; Janion, Marianna; Wencel-Wawrzeńczyk, Agnieszka; Sikorski, Marek; Wojarska, Izabela (Medical Studies/Studia Medyczne, 2017)
Physiological changes occurring during pregnancy, at the time of childbirth, and in the postpartum period may influence the occurrence, and increase in intensity of, heart rhythm abnormalities. There is insufficient data on the safety and effectiveness of pharmacological treatment in the group of pregnant women. Cardiac arrhythmia induced by pregnancy rarely requires introduction of pharmaceuticals. It should be noted that most antiarrhythmic agents are not recommended for use during pregnancy and the breastfeeding period. In cases where a drug use is necessary, the most popular choice is -blockers or a calcium channel blocker – verapamil, which does not have teratogenic effects, but does get transferred to the mothers’ milk. The presented case study concerns a woman with no structural heart defects in her third pregnancy, with very ill-tolerated ventricular arrhythmia.